Effective-component compatibility of Bufei Yishen formula protects COPD rats against PM2.5-induced oxidative stress via miR-155/FOXO3a pathway - Jiansheng Li (Elsevier, 2021)
Ambient particulate matter <2.5 µm (PM2.5) has been identified as a critical risk factor in chronic obstructive pulmonary disease (COPD) exacerbation, but therapies for this condition are limited. Effective-component compatibility of Bufei Yishen formula (ECC-BYF) exhibits beneficial efficacy on COPD rats. However, its effect on PM2.5-aggravated COPD rats are considered to be uncertain. In this study, we used an established PM2.5-aggravated COPD rat model in vivo to evaluate the protective effect of ECC-BYF, and focused on its antioxidative role in PM2.5-stimulated bronchial epithelial cells via regulating microRNA (miR)−155/ forkhead box class O3a (FOXO3a) pathway. As expected, PM2.5-aggravated COPD rats showed a reduction of lung function, persistent lung inflammation, and remodeling of lung tissue. In comparison, ECC-BYF administration significantly enhanced lung function, alleviated alveolar destruction, inflammatory cell infiltration, mucus hypersecretion, and collagen deposition, along with diminishing inflammatory cytokine production and oxidative stress. Furthermore, ECC-BYF pretreatment markedly decreased the fluorescence intensity of reactive oxygen species (ROS) in PM2.5-induced human bronchial epithelial (Beas-2B) cells and primary mouse tracheal epithelial cells (MTECs), as well as reversing the imbalance between oxidants and antioxidants in Beas-2B. Meanwhile, ECC-BYF elevated FOXO3a while inhibiting miR-155 expression dose -dependently. In vitro transfection of miR-155 mimic into Beas-2B significantly decreased FOXO3a protein expression, accompanied by the reduced superoxide dismutase 2 (SOD2) and catalase (CAT) expressions, thus eliminating the protective effect of ECC-BYF on PM2.5-evoked oxidative stress. Nonethless, FOXO3a overexpression could partially restore the antioxidative effect of ECC-BYF. In conclusion, ECC-BYF can protect pre-existing COPD against PM2.5 contamination by exerting a profound antioxidative influence via regulating miR-155/FOXO3a signaling.